(untitled) (Heritage, 2022)
For many years, the role of women in Serbia was in an unenviable position. Serbian women often faced numerous limitations and challenges, including the inability to educate, participate in the public sphere, and decide to lead their own lifestyles. However, with the social changes in Serbia, in the middle of the 19th century, the emancipation of women began. Despite being slow, often insufficiently organized, the first steps towards changing the role of women helped women, over time, to be more encouraged, motivated and united. The situation was similar in all cities, including in Prizren. Starting from the founding of the first private women’s schools all the way to women’s craft schools, young girls were given the opportunity to be educated and develop various skills. Apart from schools, women in Prizren also acquired knowledge in women’s humanitarian associations, which were the main gathering places for women’s activism in the 19th and 20th century. In this regard, the aim of the paper is to provide an overview of the general position of women in Serbia in the mentioned period, to present the education of female children in Prizren, as well as to point out the existence of two influential women’s associations - Women’s Charity Society "Srpkinja" and the Circle of Serbian Sisters, which are mostly responsible for education, humanitarian work, participation in city activities and the overall development of female generations in Prizren.